KONTRIBUSI PEGAWAI DALAM MANAJEMEN SEKTOR PUBLIK TERHADAP PENGELOLAAN BERKAS RUMAH TANGGA BIRO UMUM SETDA PROVINSI JAWA TIMUR - Permana, Linang Rizkika Akbar Jalu; Harmawan, Bagus Nuari (Jurnal Progress Administrasi Publik, 2024)
Nowadays the modern management system involves a wider role on the performance of public sector organizations. In developing a management system, it also requires good human resources and is able to carry out all the tasks for which it is responsible. The ability of human resources can be influenced by their educational background. Because the form of the ability of each human resource is taaught and obtained from the level of Education. These human resources will be able to influence the implementation of an effective and efficient management system. If the management system runs effectively and efficiently, the goals of each organization can be realized to the maximum. In this article discusses the management system in File Management in government agencies at the regional level, namely the East Java Provincial Secretariat Agency. After research found several things that have a relationship with the contribution of employees. Employees also have a contribution in building involvement and empowerment in the field of file management. Not only that, employees are also required to be able to encourage new ideas in the field of file management. And finally, employees can also contribute to creating an environment to realize personal goals and develop skills and abilities in file management. In this study aims to determine the role of employees in contributing to create good management in the process of file management in the household sub-division of the Bureau of General Secretariat of East Java. This study uses descriptive qualitative research methods with literature reviews and interviews with household employees of the East Java Secretariat General Bureau. The role of employees is very important for the development of management systems in a public sector organization.   Keywords: Public Sector Organizations; Management; Employees